Essure® for management of hydrosalpinx prior to in vitro fertilisation—a systematic review and pooled analysis. (3rd January 2014) - Arora, P; Arora, RS; Cahill, D
<x xml:space="preserve">Abstract</x> Background Hydrosalpinges in infertile women reduce the success of in vitro fertilisation (IVF) by 50%. Surgical management of hydrosalpinges before IVF improves outcome but these procedures are often contraindicated in women with dense pelvic adhesions. Tubal occlusion achieved by Essure® via hysteroscopy provides an alternative. Objectives To conduct a systematic review on the efficacy and safety of Essure® in the management of hydrosalpinx before IVF. Search strategy We searched MEDLINE (January 1950 to July 2013), EMBASE (January 1980 to July 2013) and Web of Science (1899 to July 2013). We also searched reference lists of relevant articles and proceedings of relevant international conferences (2000–2013). Selection criteria All types of studies where women with suspected infertility and presence of hydrosalpinx had hysteroscopic tubal occlusion with Essure® before IVF. Data collection and analysis Two authors independently selected studies and extracted data. Where necessary, study authors were contacted for further data. Main results In all, 115 women in 11 studies received Essure®, mainly in the outpatient setting where local anaesthesia by paracervical block and/or intravenous sedation was used. Successful placement of Essure® was achieved in 96.5% (95% confidence interval [95% CI] 91.1–98.9%) of women and tubal occlusion in 98.1% (95% CI 93.1–99.9%). Subsequent IVF resulted in 38.6% pregnancy rate (95% CI 30.9–46.8%), 27.9% live birth rate (95% CI 21.1–35.8%) and 28.6% combined ongoing pregnancy and live birth rate (95% CI 21.7–36.6%) per embryo transfer. Author's conclusions Essure® appears to be an effective option for management of hydrosalpinx in women before IVF although evidence from a randomised controlled clinical trial is lacking.